Students’ Response on Developing Writing Descriptive Text Material Using Genre Based Approach - Mu'man Mu'man; Setya Resmini (Universitas Veteran Bangun Nusantara, 2023)
The ability of writing narrative text is one of the skills that have to be mastered by students because writing is one of four basic skills in English. This research aims to identify students’ response on developing writing narrative text material using genre-based approach. The method of this research used research and development with the instruments – questionnaire and interview. Then the subject of the research is seventh grade students in one of junior high school in Cimahi. The result of this research is students’ responses towards the material during a field test were categorized as very good with some notes to point out: the product assists students to learn to write descriptive text; the design and graphics of the product are visually appealing; and the product has met the students' own criteria for a good material. On the other hand, based on their own experience of using the product, they had obstacles in understanding the material. Thus, it was considered in revising the product to simplify the language and task instruction.